RrTTG1 promotes fruit prickle development through an MBW complex in Rosa roxburghii - Huang, Xiaolong; Yi, Peipei; Liu, Yanjing; Li, Qiaohong; Jiang, Yu; Yi, Yin; Yan, Huiqing (Frontiers in Plant Science, 2022)
Fruit prickles are widely distributed on the pericarp and exhibit polymorphic traits at different developmental stages. Although they are multicellular appendages that are well-known for helping plants defend against biotic and abiotic stresses, their origination and molecular mechanism are still less known. Here, we studied the origination and molecular mechanism of fruit prickles in Rosa roxburghii. Using morphological and histological observations, we found that the fruit prickle primordium of R. roxburghii originated from the ground meristem that underwent cell division to form flagelliform prickles, continued to enlarge, and finally lignified to form mature fruit prickles. We amplified a homolog of candidate gene TRANSPARENT TESTA GLABRA1 (TTG1) from R. roxburghii, named RrTTG1. RrTTG1 harbored four conserved WD-repeat domains and was exclusively nuclear-localized. Using qRT-PCR and in situ hybridization, we found that RrTTG1 was constitutively expressed and highly expressed during the initiation and cell expansion phases of fruit prickles. Ectopic expression analysis in Arabidopsis proved that RrTTG1 substantially enhanced the number of trichome and pigmentation production and inhibited root hair formation. Besides, RrTTG1 complemented the phenotypes of the ttg1 mutant in Arabidopsis, thus indicating that RrTTG1 played pleiotropic roles akin to AtTTG1. We demonstrated that the RrTTG1 only interacted with RrEGL3, a homolog of ENHANCER OF GLABRA3 (EGL3), via yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays. Briefly, RrTTG1 might positively regulate the initiation of fruit prickle primordium and cell enlargement by forming the RrTTG1-RrEGL3-RrGL1 complex in R. roxburghii. Therefore, our results help characterize the RrTTG1 in R. roxburghii and also elucidate the establishment of the prickles regulatory system in the Rosaceae plants.